MOTOR PERFORMANCE IN SCHOOLCHILDREN OF THE DISTRICT OF BALBINA IN PRESIDENTE FIGUEIREDO/AM (Fiep Bulletin - online, 2013)
The present study, looked for to investigate the motor acting a sample of 347 subject of both sexes with age among seven to 14 years, being 166 boys and 181 girls, selected randomly in the children's population and belonging adolescents the Municipal School of the District of Balbina in President Figueiredo/AM. The study used the growth indicators and physical fitness. In agreement with the information found in this study in relation to the medium values of the variables stature anthropometrics and corporal weight in both sexes, it was verified that the girls of this study presented significant increases in all the variables with the age, demonstrating be higher and heavier than the boys of the same study. Regarding the aptitude tests physics information. The analysis of the data revealed in the variables of modified sit-up, standing long jump, modified pull-up, 30 meter-run and run/walk of nine and twelve minutes, larger indexes of the boys motor acting in relation to the girls. These values compete to affirm that the boys of this study are stronger, faster and they possess more resistance cardiopulmonary than the girls, probably because they are well more assets than the girls.
Keywords: Motor performance; Schoolchildren; Physical fitness.